Nutritive Value of Ajuga iva as a Pastoral Plant for Ruminants: Plant Phytochemicals and In Vitro Gas Production and Digestibility - Ammar, Hajer; Kholif, Ahmed; Soltan, Yosra; Almadani, Mohammad; Soufan, Walid; Morsy, Amr; Ouerghemmi, Saloua; Chahine, Mireille; de Haro Marti, Mario; Hassan, Sawsan; Selmi, Houcine; Horst, Egon; et al. (MDPI, 2023)
This study aims to evaluate the nutritive value of Ajuga iva (A. iva) harvested from three distinct altitude regions in Tunisia (Dougga, Mograne, and Nabeul). The chemical composition, phenolic concentration, gas production, and in vitro dry matter (DM) digestibility were determined. The highest concentrations of neutral detergent fiber (NDF) and acid detergent fiber (ADF) were for A. iva cultivated in Nabeul. In contrast, the highest crude protein (CP) concentration was observed in that cultivated in Mograne, and the lowest (p < 0.01) CP concentration was noted in that cultivated in Dougga. Additionally, the cultivation regions affected the concentrations of free-radical scavenging activity, total flavonoids, and total polyphenols (p < 0.01). The highest free-radical scavenging activity was observed with A. iva cultivated in Dougga and Mograne. The highest (p < 0.05) gas production rate and lag time were observed in A. iva cultivated in Mograne and Nabeul regions. DM digestibility differed between regions and methods of determination. The highest (p < 0.01) DM degradability, determined by the method of Tilley and Terry and the method of Van Soest et al., was for A. iva cultivated in Mograne and Dougga, while the lowest (p < 0.01) value was recorded for that cultivated in the Nabeul region. Likewise, metabolizable energy (ME) and protein digestibility values were higher for A. iva collected from Mograne region than that collected from the other sampling areas. In conclusion, the nutritive value of A. iva differed between regions. Therefore, care should be taken when developing recommendations for using A. iva in an entire region. Season- and region-specific feeding strategies for feeding A. iva are recommended.